Supraglacial ice cliffs and ponds on debris-covered glaciers: spatio-temporal distribution and characteristics - Steiner, Jakob F.; Buri, Pascal; id_orcid:0 000-0003-3890-2109; Miles, Evan S.; Ragettli, Silvan; Pellicciotti, Francesca (International Glaciological Society, 2019)
Ice cliffs and ponds on debris-covered glaciers have received increased attention due to their role in amplifying local melt. However, very few studies have looked at these features on the catchment scale to determine their patterns and changes in space and time. We have compiled a detailed inventory of cliffs and ponds in the Langtang catchment, central Himalaya, from six high-resolution satellite orthoimages and DEMs between 2006 and 2015, and a historic orthophoto from 1974. Cliffs cover between 1.4% (± 0.4%) in the dry and 3.4% (± 0.9%) in the wet seasons and ponds between 0.6% (± 0.1%) and 1.6% (± 0.3%) of the total debris-covered tongues. We find large variations between seasons, as cliffs and ponds tend to grow in the wetter monsoon period, but there is no obvious trend in total area over the study period. The inventory further shows that cliffs are predominately north-facing irrespective of the glacier flow direction. Both cliffs and ponds appear in higher densities several hundred metres from the terminus in areas where tributaries reach the main glacier tongue. On the largest glacier in the catchment ~10% of all cliffs and ponds persisted over nearly a decade. ISSN:0022-1430 ISSN:1727-5652